2014
DOI: 10.11144/javeriana.sc19-3.selh
|View full text |Cite
|
Sign up to set email alerts
|

Situación epidemiológica de la leptospirosis humana en Centroamérica, Suramérica y el Caribe

Abstract: To identify and describe the epidemiological status of human leptospirosis or Weil's disease, we searched scientific publications and reports issued by health control authorities from 2006 to 2013. Information extraction was done independently and the methodological quality of the articles was evaluated using a checklist created for that purpose. The country with the highest incidence of human leptospirosis was Trinidad & Tobago (22 cases per 100,000 people) and the highest percentage of cases occurred in Guya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
0
4
0
4
Order By: Relevance
“…Most previous studies have evaluated regional incidence of human leptospirosis at department scale in Colombia 15,16,30,31,32 , and to the best of our knowledge, our study is the first that demonstrates the existence of four hotspots of high human leptospirosis incidence at municipal level. At the regional level, our results are consistent with those observed by other authors, particularly in the Uraba region 33 .…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Most previous studies have evaluated regional incidence of human leptospirosis at department scale in Colombia 15,16,30,31,32 , and to the best of our knowledge, our study is the first that demonstrates the existence of four hotspots of high human leptospirosis incidence at municipal level. At the regional level, our results are consistent with those observed by other authors, particularly in the Uraba region 33 .…”
Section: Discussionmentioning
confidence: 57%
“…A prevalence of over 90% in Rattus rattus, Rattus norvegicus and Mus musculus has also been documented 12,13 . However, in humans, some studies have reported seroprevalences ranging from 6% to 27.7% 14 , and the circulation of 17 serovars has been recorded in the country 15,16 .…”
Section: Introductionmentioning
confidence: 99%
“…El diagnóstico microbiológico se puede realizar mediante varias técnicas siendo la aglutinación microscópica el estándar de oro. El tratamiento es de soporte y el inicio temprano de la terapia antimicrobiana es clave para acortar la duración de la enfermedad 2,3 . El conocimiento de esta enfermedad re-emergente en el mundo es fundamental en el personal de salud que atiende población pediátrica, debido a que, un diagnóstico precoz y un tratamiento oportuno impacta en la calidad de vida los pacientes.…”
Section: Zoonosisunclassified
“…En Latinoamérica se han registrado brotes en diferentes países como Brasil, Nicaragua y República Cooperativa de Guyana 7 . Sin embargo, no se tiene un registro claro de los casos por la variación en los sistemas de vigilancia epidemio-lógica, ya que, no se conoce con claridad el inicio en la implementación de notificación obligatoria en diferentes países como El Salvador, Honduras y República Dominicana; a diferencia de Chile y Argentina quienes llevan un reporte desde el año 2002, y en Colombia desde 2007 3,8 . El cambio climático global ha sido uno de los principales contribuyentes en la aparición de leptospirosis, como es el caso de brotes en América Central y América del Sur debido a inundaciones por el Fenómeno del Niño 2 .…”
Section: Epidemiologíaunclassified
“…La bacteria se restringe principalmente en los túbulos renales de los animales portadores, habitando persistentemente este sitio para luego ser eliminados por la orina, presenta una gran variedad de signos y síntomas por lo que existen varios diagnósticos diferenciales (5). Para efectuar un buen diagnóstico, la Organización Mundial de Sanidad Animal(OIE) recomienda como prueba de oro la Aglutinación Microscópica o Microaglutinación (MAT) (6).…”
Section: Introductionunclassified